Answer:
(- 1, - 2 )
Step-by-step explanation:
Given the 2 equations
x - 3y = 5 → (1)
5x - 2y = - 1 → (2)
Rearrange (1) expressing x in terms of y by adding 3y to both sides
x = 5 + 3y → (3)
Substitute x = 5 + 3y in (2)
5(5 + 3y) - 2y = - 1 ← distribute left side
25 + 15y - 2y = - 1
25 + 13y = - 1 ( subtract 25 from both sides )
13y = - 26 ( divide both sides by 13 )
y = - 2
Substitute y = - 2 in (3) for corresponding value of x
x = 5 + (3 × - 2) = 5 - 6 = - 1
Solution is (- 1, - 2 )
Answer:
12x-3x
= 9x
Step-by-step explanation:
Hope it is helpful....
Each best behaved class will receive 1.5 pounds of candy.
To get his answer you just have to divide 15 by 10
15 divided by 10 = 1.5 pounds
Answer:
uh, the answer is either (-6, 1) or (-1,6) because the when plugging them both into the equation, they're both true.